Analisis Kesulitan Membaca Permulaan Siswa Kelas II Sekolah Dasar - Aldinna Shoffiya Rahmaddanti; Dedy Irawan (Universitas Maritim AMNI Semarang, 2023)
The most common learning difficulties faced by Primary school students are difficulties in learning to read. In second-grade students of SD Negeri 4 Dukuhwaluh, this problem was also found, so this study aims to describe students' initial reading difficulties. This research used a descriptive qualitative research method of a case study. The subjects of this study included 9 students who had difficulty in reading, class teachers, and 9 students' parents. Observation, interviews, and document analysis were used to collect data. The validity test of the data used data and technique triangulations. Data analysis techniques used the Miles Huberman model; data collection, data reduction, data presentation, and drawing conclusions. Reading difficulties for second-grade students of SD Negeri 4 Dukuhwaluh were experienced by 9 students. The results showed that initial reading difficulties included the following: a) difficulty in recognizing letters, there were 2 students who did not recognize letters from A to Z. b) difficulty in reading diphthongs, there were 4 students who did not want to pronounce any letters or stuttered when reading diphthongs. c) difficulty in reading words, there were 4 students who were not fluent in reading words or were still spelling. d) not proficient in reading consonants, there were 2 students who only knew a few consonants, and e) not yet fluent in reading sentences, there were 9 students who were still not fluent in reading sentences. It can be concluded that the difficulties experienced by the 9 students were various.